Uma proposta de ensino do ecoico como facilitador para o ensino do mando em crianças com autismo. - Giolo, Mayara C Freitas Pereira (2024)
The teaching of verbal behavior to individuals with autism, using the verbal operant described by Skinner, is a widely explored topic in research. This study aimed to systematically review the literature to identify effective procedures for teaching vocal manding to individuals with autism, develop a teaching protocol for the mand operant, and investigate whether the teaching of echoic and mand behavior can promote the emergence of other mands. A systematic review was conducted as the first study, revealing how mand teaching is structured in Applied Behavior Analysis and identifying significant gaps that can be addressed with standardized procedures. Based on these findings, a mand teaching protocol was developed, grounded in the teaching of echoic behavior. This protocol was tested on eight children aged 1 to 6 years diagnosed with autism, using two experimental designs: a reversal design in the second study and a multiple-probe design in the third study. The results showed that all participants were able to emit mands, including for absent items. Of the eight participants, seven also demonstrated new mands after the teaching, even without direct instruction for these. The application of this protocol to a larger number of individuals and with increased exposures could potentially enhance speech teaching in children with autism who do not yet have a vocal repertoire.